Filmfordítás vagy filmferdítés? A filmfordítás problémájáról - Debreceni, Ferenc (Studia Litteraria, 2020)
The paper discusses a specialised branch of translation, lm translation, more precisely subtitle translation. Film subtitle translation is not only difficult for its linguistic and cultural aspects but for its technical challenges as well. The translation needs to comply with such technical criteria as the length of the subtitle, the timeframe for reading, and in certain cases the lip movement of the actor in the lm. In the last section of the article the author demonstrates his previously made points by sharing his experiences with the translation of The Aristocratic Peasant Girl by Russian director Aleksey Sakharov.